Tutela jurisdicional que concede a tutela antecipada antecedente estabilizada e seus efeitos - Bernardini, Carlos Eduardo Jorge (2016)
The scope of this dissertation consists in analyzing the non-ordinary court protection and its possibility of stabilization regarding preliminary relief and its effects. The work analyses its characters, limitations and possible effects that these kind of decision may have. For this, it is analyzed the concept of court protection, some historical aspects and classification. In light of those concepts, it will be analyzed the non-ordinary court protection types, provision proceedings (preliminary relief), evidence court decision, especially in regards to the New Procedure Civil Code. Furthermore, it will be developed the new ruling concept and some constitutional principles, such as due process of law, the principle of equality and critical Court precedents that encompass the subject matter. In addition, in this chapter cognition techniques will be pointed out and analyzed. We addressed the topic of the unappealeble decisions, historical aspects and classification settling a comparison among CPC/73 and CPC/15. Finally, the preliminary injunction will be analyzed; its proceedings stated in the CPC/15 and some critical aspects